Analysis of spatial differentiation and influencing factors of rural industrial integration efficiency in China - Yuan Fang; Ying Yang (PLoS ONE, 2025)
The integrated development of rural industries is a primary method to accelerate rural revitalization, a practical path to promote agricultural and rural modernization, and an important means to build a strong agricultural nation. Based on the super-efficiency EBM model, rural industrial integration efficiency in the east, central and west regions of 31 provinces (municipalities and autonomous regions) in China from 2012 to 2022 is measured, and the spatial differentiation, dynamic distribution and influencing factors of rural industrial integration efficiency are analyzed by using Dagum Gini coefficient, Kernel density estimation and Tobit model, respectively. The study shows that the core driving forces of rural industrial integration efficiency in the east, central and west regions are pure technical, comprehensive and pure technical efficiency, respectively; hyper-variable density is the main source of spatial differentiation; serious divergence in rural industrial integration efficiency in the east; there is regional heterogeneity in the impact of different factors on the efficiency of rural industrial integration. It is necessary to strengthen the structure of financial inputs, establish an efficiency assessment system, and enhance the infrastructure and public services.